Kenya Economic Update, June 2014, No. 10 : Take Off Delayed? - World Bank (Washington, DC, 2014)
Kenya's economy remains strong, enabling it to weather the headwinds it faces. Maintenance of macroeconomic stability and adherence to credible policies has underpinned Kenya's growth in the past. Continuing to adhere to these policies will help the country surmount domestic shocks, allowing it to grow 4.7 percent a year in 2014 and 2015. Addressing the pressures emerging from fiscal expansion is a priority. The large public sector wage bill and devolution have reduced fiscal buffers and increased fiscal risks. Kenya's health outcomes are not commensurate with its aspirations of achieving middle income status. Global evidence indicates that investing in primary health care is the most cost-effective way to improve health outcomes. Key recommendations to stabilize and sustain a robust growth include: (a) deepening fiscal consolidation without reducing infrastructure spending; and (b) expanding the engines of growth to include not only consumption but also investments and exports. Key recommendations that can help Kenya improve the delivery of primary health care include: (a) focusing first on making existing public primary health care facilities operational; (b) building on partnerships with faith-based organizations and partner with the private sector; and (c) the use of fixed facilities, such as inpatient services in many health centers that are grossly underutilized.